Avtobiografskost sodobne slovenske kratke proze - Bošnjak, Blanka (Jezik in slovstvo, 2008)
In view of the ascertained phenomenon of genre syncretism and new genre constructions in contemporary literature, which are often also combinations of literary and non-literary genres (in our case of the research of the combination of various forms of contemporary Slovene short prose, such as travelogue, essay, memoires, etc, and biography), interesting characteristics and possibilities of manifestation have crystallized on the basis ofthe analysis of selected texts of Slovene short prose from the last ten years. These can be counted amongst the following forms of literary autobiography that appear in the selected short prose texts: memoir autobiography, memoire collage, travelogue andfictional autobiography. Analysis of these texts has shown a situation that is linked with the contemporary understanding of literary discourse, as well as with the system ic and functional placement of literature in the production and reception context.
Keywords: avtobiografska proza; comparative literature; kratka proza; literarne študije; primerjalna književnost; Slovene literature; slovenska književnost